Development of ultralow-background cryogenic calorimeters for the measurement of surface α contamination. (March 2023) - Benato, G.; Biassoni, M.; Brofferio, C.; Celi, E.; Dell'Oro, S.; Drobizhev, A.; Gianvecchio, A.; Girola, M.; Ghislandi, S.; Kolomensky, Yu.G.; Nutini, I.; Olmi, M.; et al.
Abstract: Next-generation experiments searching for rare events must satisfy increasingly stringent requirements on the bulk and surface radioactive contamination of their active and structural materials. The measurement of surface contamination is particularly challenging, as no existing technology is capable of separately measuring parts of the 232 Th and 238 U decay chains that are commonly found to be out of secular equilibrium. We will present the results obtained with a detector prototype consisting of 8 silicon wafers of 150 mm diameter instrumented as bolometers and operated in a low-background dilution refrigerator at the Gran Sasso Underground Laboratory of INFN, Italy. The prototype was characterized by a baseline energy resolution of few keV and a background < 100 nBq/cm 2 in the full range of α energies, obtained with simple procedures for cleaning of all employed materials and no specific measures to prevent recontamination. Such performance, together with the modularity of the detector design, demonstrate the possibility to realize an alpha detector capable of separately measuring all alpha emitters of the 232 Th and 238 U chains, possibly reaching a sensitivity of few nBq/cm 2 . Highlights: Material screening. Bolometric alpha detector. Low-radioactivity measurements.